Objective reporting or mouthpiece for the opposition groups?: a study of MalaysiaKini coverage of the 2013 Malaysian general election - Mohd Faizal Kasmani, (Penerbit Universiti Kebangsaan Malaysia, 2016)
MalaysiaKini is regarded by political communication scholars as an influential online news medium in Asia. Within the restricted environment of Malaysian media, MalaysiaKini is able to provide critical reports of the ruling authorities and gives voice to the marginalised opinions of the opposition groups. MalaysiaKini is often praised for its high standards of journalistic practice based on the norms and values of independent journalism. Some however argue that as the platform for marginalised voices, the news portal is also, by default, seen as pro-opposition and acts as an opposition mouthpiece in Malaysia. This article examines the coverage of the news portal, and the 2013 Malaysian General Election will be used as a case study. Drawing on one of the important concepts in modern journalistic practice, namely objectivity, this study attempts to explain the extent to which MalaysiaKini fairly represents each leading side in the political controversy and in the impartial reporting of news. Through qualitative analysis, this study found that MalaysiaKini largely upholds the voice of the opposition parties. The study concludes that rather than offering objective reporting, MalaysiaKini contributes to an environment of a multiplicity of ideas and plurality of news coverage in Malaysia.